WAKTU OPTIMUM FERMENTASI LIMBAH PULP KAKAO (Theobroma cacao L.) MENGGUNAKAN KULIT BAKAU (Sonneratia sp.) DALAM PRODUKSI BIOETANOL - Kristiani K, Putu; Sabarudin, La Ode; Melati, Rima; Haeruddin, Haeruddin (Program Kreativitas Mahasiswa - Penelitian, 2013)
Bioethanol is ethanol that produce by glucose fermentation (sugar) that continuo by distillation process.  The one matter that can be use as basic materials of bioethanol that is liquid waste of pulp cocoa that coming from waste cocoa plantage  the one composer component of pulp liquid is sugar as 8-13 %. With the sugar component, so the pulp liquid as economical it can be use as the basic material the making of bioethanol by fermentation process. This research aim to produce bioethanol from the liquid waste of cocoa pulp. (Theobroma cocoa L) by using mangrove skin (sonneratia sp.). As the pure inhibitor formation of acetic acid  by the fermentation further become ethanol. The mangrove skin play role to accelerate the fermentation process to produce ethanol. It also can hamper  (inhibitor) the fermentation process  continuing  became acetic acid. The data analysis in this research use complete random plane with the time variable fermentation and repetition is done  as may as 3 time. The result of the research show that the optimum time of fermentation it is in the 12 day, by 7,5 gram mangrove skin powder, pH 5 and the fermentation temperature  25-30 0C (ROOM TEMPERATURE) it gets level of alcohol 7,69 %.Keywords: bioethanol, fermentation, cocoa pulp, mangrove skin.